Analysis of Accuracy of Evaluating the Structure of a Harvester Operator’s Workday by Work Sampling - Grzegorz Szewczyk; Dariusz Kulak; Arkadiusz Stańczykiewicz; Jiri Dvořák; Krzysztof Kamiński; Janusz M. Sowa (Croatian Journal of Forest Engineering, 2016)
The study covered an analysis of the accuracy level of measuring time within a working shift using the method of regular snapshot observation at a harvester operator’s worksite in Scots pine stands. A conformance level of the analyzed methods was evaluated through assessing the accuracy of rectilinear fitting of time structures, established using the photography of work day method and snapshot observations. The accuracy of snapshot measurements performed in 3-minute intervals was determined as high, exceeding 95%. Increasing the time interval between observations to 10 or 15 minutes resulted in higher estimation error in snapshot observation time, ranging between 5 and 10% for late thinned and clear-cut stands. The accuracy of evaluating proportions of specific work times within a working shift, in regular snapshot observations, was correlated with work cyclicality. The strongest work cycle in thinned stands consisted of 43 activities, with total duration of 13 minutes, whereas in clearcut stands it comprised 45 activities, with total duration of 15 minutes. One of the advantages of the described method, apart from its lower labour intensity as compared to working day photography, was the possibility to assess labour time and breaks as well as estimate the share of downtime.